PENJADWALAN PERAWATAN DENGAN METODE CAMPBELL DUDEL SMITH (CDS) UNTUK MENINGKATKAN PRODUKSI MESIN RECYCLE WASTE TEMBAKAU - Anggara, Teuku; Pratikto, Pratikto; Sonief, Achmad As?ad (Rekayasa Mesin, 2020)
The Campbell Dudek Smith (CDS) method is commonly used by large companies to help them make Flowshop schedules. The purpose of this study is to design a more effective maintenance scheduling sequence in order to increase the amount of production with the most efficient use of time without having to stop production and be able to calculate the productivity of the machine it self. Partial Productivity (PP) analysis is used to determine the level of machine productivity by proving Partial Productivity (PP) after is better than Partial Productivity (PP) before. This research was conducted at PT. X, one of the leading national companies in producing cigarette products such as SKT cigarettes, SKM and SPM. As a result, this study has performed calculations using the Campbell Dudek Smith (CDS) algorithm and calculates the productivity of each iteration using Partial Productivity (PP). The recommended improvement of the engine maintenance scheduling sequence is by applying the scheduling sequence to the 5th iteration, J2-J4-J3-J1-J5.